1996
DOI: 10.1007/bf01709543
|View full text |Cite
|
Sign up to set email alerts
|

Severe community-acquired pneumonia in ICUs: Prospective validation of a prognostic score

Abstract: This index, which performs well in classifying patients at high-risk of death, may help physicians in initial patient care (appropriateness of the initial antimicrobial therapy) and guide future clinical research (analysis and design of therapeutic trials).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 26 publications
1
40
0
1
Order By: Relevance
“…Nearly all of the patients required assisted ventilation. By contrast, the mortality rate in a large multicentre study of severe CAP in four French ICUs reported a mortality rate of 35% with a ventilation rate of only 52%74 [ Ib ]. Similar figures were reported from another ICU based study in France75[ II ].…”
Section: Incidence Mortality and Economic Consequencesmentioning
confidence: 99%
See 4 more Smart Citations
“…Nearly all of the patients required assisted ventilation. By contrast, the mortality rate in a large multicentre study of severe CAP in four French ICUs reported a mortality rate of 35% with a ventilation rate of only 52%74 [ Ib ]. Similar figures were reported from another ICU based study in France75[ II ].…”
Section: Incidence Mortality and Economic Consequencesmentioning
confidence: 99%
“…In the intensive care setting septic shock, defined as (a) a sustained decrease (for at least 1 hour) in systolic blood pressure of at least 40 mm Hg from baseline or (b) a resultant systolic blood pressure of <90 mm Hg after adequate volume replacement in the absence of antihypertensive drugs occurring more than 12 hours after admission to the ICU is an additional adverse sign74 [ II ],185 [ II ].…”
Section: Severity Assessmentmentioning
confidence: 99%
See 3 more Smart Citations